The repurposing of acetylsalicylic acid as a photosensitiser to inactivate the growth of cryptococcal cells - Ogundeji, Adepemi O.; Mjokane, Nozethu; Folorunso, Olufemi S.; Pohl, Carolina H.; Nyaga, Martin M.; Sebolai, Olihile M. (MDPI, 2021)
Photodynamic treatment (PDT) is often successful when used against aerobic microbes, given their natural susceptibility to oxidative damage. To this end, the current study aimed to explore the photodynamic action of acetylsalicylic acid (ASA; aspirin, which is commonly used to treat non-infectious ailments), when administered to respiring cryptococcal cells. The treatment of cryptococcal cells, i.e., exposure to 0.5 or 1 mM of ASA in the presence of ultraviolet light (UVL) for 10 min, resulted in a significant (p < 0.05) reduction in the growth of tested cells when compared to non-treated (non-Rx) cells, i.e., no ASA and no UVL. The treated cells were also characterised by diseased mitochondria, which is crucial for the survival of respiring cells, as observed by a significant (p < 0.05) loss of mitochondrial membrane potential (DYM) and significant (p < 0.05) accumulation of reactive oxygen species (ROS) when compared to non-Rx cells. Moreover, the photolytic products of acetylsalicylic acid altered the ultrastructural appearance of treated cells as well as limited the expression levels of the capsular-associated gene, CAP64, when compared to non-Rx cells. The results of the study highlight the potential use of ASA as a photosensitiser that is effective for controlling the growth of cryptococcal cells. Potentially, this treatment can also be used as an adjuvant, to complement and support the usage of current anti-microbial agents.
Keywords: Acetylsalicylic acid (ASA, aspirin); Capsule; CAP64; Cryptococcus; Membrane potential; Photodynamic treatment; Photosensitiser; Ultrastructure